Diagnóstico sectorial de la actividad venta al por mayor de productos farmacéuticos incluso veterinarios del cantón Loja - Cordero Alberca, Jhinela Alexandra (2023)
The pharmaceutical commercial sector is highly competitive because, nowadays, countless stores sell drugs; therefore, they require wholesale suppliers, either laboratories or distributors. To remain in the market, these companies constantly seek to innovate and therefore need to evaluate their performance and compare themselves with their competitors, hence the purpose of this research, whose objective is to develop a sectoral diagnosis of the wholesale activity of pharmaceutical products, including veterinary products in Loja canton. This research had a mixed approach, combining quantitative and qualitative processes with exploratory, descriptive, and field research since the topic is relatively new. In order to achieve the objectives, techniques such as the bibliographic review and the application of surveys to 31 sector representatives were used. As a result, a characterization of the sector was presented, including the sector's entry barriers, such as high competitiveness, constant innovation, and regulation; critical success factors were identified concerning the main activities, such as purchasing with economies of scale and wholesale; and key performance indicators and sector statistics were calculated. In conclusion, the commercial pharmaceutical sector prioritizes the control of its inventory, considered its most important asset, which is generally financed through financial leverage, which was 137%, providing a net profit of 15% on average.